FPGA-Based Video Acquisition System Design for Driving Recorders - Zhuangwen Wu, Xincheng Sun, Dongdong Ge (Design Engineering, 2020)
In addition to high stability and a wide field of view, high image resolution and transmission rates are expected as well. However, the images recorded under complex dynamic complex conditions and long operation are often the most important for later use. Therefore, those images urgently require fast transmission and preservation. Yet, most driving recorders use the USB 2.0 transmission protocol, which largely restricts the transmission of video images from high-resolution driving recorders. To improve the video transmission speed of driving recorders, this study presents an image preprocessing method based on field programmable gate array (FPGA) monitoring and USB 3.0 transmission. Without damaging the original structure of a driving recorder, the video images are monitored in real time through the external FPGA system, and the image data are preprocessed and restored to the host computer. Compared to the traditional transmission method, the experiment shows that our method is robust and efficient. The new method also has the characteristics of high integration, flexible use, and a user-friendly interface. It can provide new ideas and solutions for improving image processing speed in the fields of pattern recognition and machine vision.